The Emergence of Archaeology as Scientific Discipline - Ph. Subroto (Humaniora, 1997)
It might be useful to mention of definition the archaeology, since the various definitions of Archaeology might reflect the emergence and the growth of archaeelogy itself. The word "archaeology" was first used to mean ancient history in general. By this definition, the contents of archaeology are derived from various collections of old manuscripts (Daniel, 1967:1). Archaeology has an alliance with history and anthropology. Both archaeology and history deal with the human past, concerned with the narration of the past and With its explanation.